Decree No. 216 of the year 2016 determining the establishments committed to institute functional agencies and committees for occupational safety and health and ensuring labour environment security and the entities assuming the training and the rules to be followed in this respect = قرار رقم 216 لسنة 2016 بشأن تحديد المنشآت التي تلتزم بإنشاء أجهزة وظيفية ولجان للسلامة والصحة المهنية وتأمين بيئة العمل والجهات التي تتولى التدريب والوقاعد التي تتبع في هذا الشأن. (2025)
Ministry of manpower decree no. 216 of the year 2016 determining the establishment committed to institute functional agencies and committees for occupational safety and health and ensuring labour environment security, and the entities assuming the training, and the rules to be followed in this respect وزارة القوى العاملة قرار رقم 216 لسنة 2016 بشأن تحديد المنشآت التى تلتزم بإنشاء أجهزة وظيفية ولجان للسلامة والصحة المهنية وتأمين بيئة العمل والجهات التى تتولى التدريب والقواعد التى تتبع فى هذا الشأن